2016
DOI: 10.1080/10871209.2016.1198852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Message Framing and Past Experience on Intentions to Prevent Human–Coyote Conflicts

Abstract: To test the effects of message framing on intentions to participate in seven behaviors to prevent coyote problems, we randomly assigned 461 participants to a control (no message) group or one of four experimental (message) conditions, as part of a 2 (gain versus loss) x 2 (family-referencing versus community-referencing) between-subjects factorial design. We found a significant three-way interaction between gain versus loss framing, point of reference, and past experience with coyotes on intentions to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…By focusing on collective factors, practitioners orient their efforts toward more malleable factors where they may find greater success inspiring attractant securing behavior. Although the efficacy of outreach campaigns to reduce wildlife conflict is rarely tested (Gore et al 2016), with only a few examples in the literature (Saypanya et al 2013;Lu et al 2016Lu et al , 2018, our findings echo ≥1 study that reported norms can be powerful tools in wildlife-related behavior change campaigns. In a study on the use of bear-resistant storage containers in Colorado, USA, Young (2018) reported that although there were no differences in uptake of attractant securing behavior between people who received messages that emphasized the benefits of securing attractants versus those receiving messages about the risks of not securing attractants, subjective norms did significantly predict intention to secure bear attractants.…”
supporting
confidence: 72%
“…By focusing on collective factors, practitioners orient their efforts toward more malleable factors where they may find greater success inspiring attractant securing behavior. Although the efficacy of outreach campaigns to reduce wildlife conflict is rarely tested (Gore et al 2016), with only a few examples in the literature (Saypanya et al 2013;Lu et al 2016Lu et al , 2018, our findings echo ≥1 study that reported norms can be powerful tools in wildlife-related behavior change campaigns. In a study on the use of bear-resistant storage containers in Colorado, USA, Young (2018) reported that although there were no differences in uptake of attractant securing behavior between people who received messages that emphasized the benefits of securing attractants versus those receiving messages about the risks of not securing attractants, subjective norms did significantly predict intention to secure bear attractants.…”
supporting
confidence: 72%
“…A communication frame organizes one’s everyday reality by attaching meaning to the unfolding of events (Chong & Druckman, 2007; Gamson & Modigliani, 1989; Tuchman, 1978). Message framing effects studies have been used to address a variety of HWC, such as food attraction with coyotes (Lu, Siemer et al, 2016), rabies exposure with bats, (Lu, McComas et al, 2016), and rule adherence during a wildlife tour with gorillas (Gessa & Rothman, 2021). In the environmental communication literature, the effectiveness of message frames tends to be context-dependent (Kolandai-Matchett & Armoudian, 2020), and so research on message framing for reducing proximity-related conflicts between people and wildlife in PPA is warranted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Coverage of coyotes as a social problem in urban environments is widespread [ 19 ]. Coyote attacks, in particular, prompt short-term increases in media coverage that not only describe the human trauma and individual problem animal but often present coyotes more broadly as pests and problems [ 17 ]. This short-term coverage negatively influences perceptions of coyotes, especially when they attack children [ 17 ].…”
Section: Background and Theorymentioning
confidence: 99%
“…Coyote attacks, in particular, prompt short-term increases in media coverage that not only describe the human trauma and individual problem animal but often present coyotes more broadly as pests and problems [ 17 ]. This short-term coverage negatively influences perceptions of coyotes, especially when they attack children [ 17 ]. Importantly, while extreme negative events like attacks on children are likely to spark justifiable concern or fear, the media often distorts neutral events in ways that amplify negative views.…”
Section: Background and Theorymentioning
confidence: 99%
See 1 more Smart Citation